The bifidobacterial distribution in the microbiome of captive primates reflects parvorder and feed specialization of the host - Modrackova, Nikol; Stovicek, Adam; Burtscher, Johanna; Bolechova, Petra; Killer, Jiri; Domig, Konrad J; Neuzil-Bunesova, Vera (Scientific reports, 2021)
Bifidobacteria, which commonly inhabit the primate gut, are beneficial contributors to host wellbeing. Anatomical differences and natural habitat allow an arrangement of primates into two main parvorders; New World monkeys (NWM) and Old World monkeys (OWM). The number of newly described bifidobacterial species is clearly elevated in NWM. This corresponds to our finding that bifidobacteria were the dominant group of cultivated gut anaerobes in NWM, while their numbers halved in OWM and were often replaced by Clostridiaceae with sarcina morphology. We examined an extended MALDI-TOF MS database as a potential identification tool for rapid screening of bifidobacterial distribution in captive primates. Bifidobacterial isolates of NWM were assigned mainly to species of primate origin, while OWM possessed typically multi-host bifidobacteria. Moreover, bifidobacterial counts reflected the feed specialization of captive primates decreasing from frugivore-insectivores, gummivore-insectivores, frugivore-folivores to frugivore-omnivores. Amplicon sequencing analysis supported this trend with regards to the inverse ratio of Actinobacteria and Firmicutes. In addition, a significantly higher diversity of the bacterial population in OWM was found. The evolution specialization of primates seems to be responsible for Bifidobacterium abundance and species occurrence. Balanced microbiota of captive primates could be supported by optimized prebiotic and probiotic stimulation based on the primate host.
Keywords: Bifidobacterium; mikrobiota; Primates; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Feces; RNA ribozomální 16S; Probiotics; primáti; Animals; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; feces; Microbiota; zvířata; RNA, Ribosomal, 16S; probiotika